Desenvolvimento e avaliação de calorimetros via nitrogênio líquido e fluxo continuo (água) para processos de soldagem - Arévalo, Hernán Dario Hernández (2011)
The correct measurement of heat input in welding processes has constantly been referred as a need for the correct understanding of physical phenomena involved in such processes. Among the different techniques available, there are experimental ones that employ different calorimeters, which can be based on water flow measurement (static and dynamic), Seebeck, isolated box and liquid nitrogen evaporated mass. These techniques present large dispersion of results for thermal efficiency of welding processes. Therefore, this work aims to present the project, construction and assessment of a liquid nitrogen calorimeter and other one based on constant flow (water) measurement. Both calorimeters were evaluated for measuring heat input and thermal efficiency of GTAW (Gas Tungsten Arc Welding) and GMAW (Gas Metal Arc Welding) processes. Different parameters were varied and the obtained results were compared to technical literature and between both calorimeters. For GTAW process, bead on plate welding was carried out with Ar as shielding gas over ASTM A36 plate, varying current, arc length, travel speed and bead length. For GMAW processes, both short-circuit and spray transfers were used with AWS ER70S-6 wire with 1,2 mm of diameter and Ar+25%CO2 (short-circuit) and Ar+5%O2 (spray) as shielding gases. For derivative processes (STT Surface Tension Transfer, RMD Regulated Metal Deposition, CMT Cold Metal Transfer, GMAW-P Pulsed and GMAW-PV Variable Polarity), the welding parameters were adopted from other researchers from Laprosolda. It can be concluded that the liquid nitrogen calorimeter presents good repeatability, with maximum difference of 3%. Also, the obtained results are coherent for different welding conditions applied through the work with global thermal efficiencies of 70,3% for GTAW, 78,6% for GMAW conventional short-circuit, 73,6% for GMAW with spray transfer and 76,1% for GMAW derivative processes. The results measured by the continuous flow (water) calorimeter followed the trend of the liquid nitrogen one, but with average results 12% lower.